Digitalization of Halal Markets and Sharia E-Comme - nurjannah, syamratun; Hidayat, Samsul; Khairunnisa, Dina; Al Faridzy, Muhammad N; Chairunnisa, Riska (ILTIZAM Journal of Shariah Economics Research, 2025)
This study aims to reassess sharia compliance and ethical consumerism in the process of halal market digitalization and the development of sharia e-commerce in Indonesia amid the era of technological disruption. The approach used is normative-fiqh combined with a comparative analysis between fiqh muamalah provisions, DSN-MUI fatwas, and Financial Services Authority (OJK) regulations, with empirical case studies on three main platforms: Tokopedia Salam, Halal.id, and Alami Sharia. The results of the study show a gap between Sharia legal norms and actual practices in the digital space, particularly in terms of electronic contracts, the potential for gharar, riba, and tadlis. DSN-MUI fatwas have provided a legal basis for digital financial innovation, but their implementation has not been integrated with a digital Sharia audit system that is adaptive to technological developments such as smart contracts and AI-based verification. Empirically, Tokopedia Salam excels in market inclusion but is weak in halal verification, Halal.id excels in product transparency but has the potential for usury in its payment system, while Alami Sharia demonstrates the strongest sharia compliance model through DSN supervision and the application of mudharabah contracts. Theoretically, this research contributes to the development of a conceptual model of the Digital Sharia Governance Framework that integrates the principles of maqasid al-syariah with digital economic governance. The practical implications encourage policy harmonization between DSN-MUI, OJK, and BPJPH to form an inclusive, transparent, and equitable digital halal ecosystem in accordance with Islamic values.